The Impact of Online Lectures on Accounting Students' Interest in Learning - Hasna Mudiarti; Agustina Eka Harjanti (Bongaya Journal for Research in Accounting (BJRA), 2021)
This research examines the effect of online lectures on student interest in learning. This research uses the Technology Acceptance Model (TAM) approach, a theory that explains the perceptions of technology users, which consists of two constructs: perceived usefulness and perceived ease of use. The population in this study were students majoring in accounting at the Kudus Regency College. Sampling using purposive sampling method and the number of samples of 98 respondents. The data obtained were analyzed using the PLS (partial least square) analysis technique through the smartPLS software. The study results found that online lectures had a positive and significant effect on the learning interest of accounting students in the Kudus Regency. This can be seen from the results of testing how perceived usefulness and perceived ease of use have a positive and significant value on student interest in learning.